2014
DOI: 10.1080/02732173.2014.978427
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Discourse? Local Media Coverage of the Terri Schiavo Case

Abstract: This article contributes to a more systematic understanding of the role of mainstream media in deliberative processes by analyzing how inclusive local newspapers are of diverse perspectives on the Terri Schiavo case. Using both Pearson’s chi-square test and multinomial logistic regression, we assess how ownership, state political ideology, geographic location, and news format affect what ideas are included in the debate over whether Terri Schiavo’s hydration and nutrition tubes should be removed as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…The same technique (and coders) were used to content analyze media coverage. For a detailed discussion of the newspaper sample, see Rohlinger, Pederson, and Valle (2015 To verify this assertion, we also conducted time-sensitive analyses (not shown) and found that the activist identity was almost exclusively used in conjunction with the e-mail campaign.…”
Section: Acknowledgmentsmentioning
confidence: 90%
See 4 more Smart Citations
“…The same technique (and coders) were used to content analyze media coverage. For a detailed discussion of the newspaper sample, see Rohlinger, Pederson, and Valle (2015 To verify this assertion, we also conducted time-sensitive analyses (not shown) and found that the activist identity was almost exclusively used in conjunction with the e-mail campaign.…”
Section: Acknowledgmentsmentioning
confidence: 90%
“…News coverage, of course, is not the only kind of content that potentially affects claims-making. Individuals are exposed to additional frames through opinion media (Jacobs and Townsley 2011; Rohlinger, Pederson, and Valle 2015), social media, and news blogs (Bichard 2006; Hamdy and Gomaa 2012; Howard and Parks 2012) as well as social movement organizations (McCarthy and Zald 1977; Rohlinger 2015). The latter, in particular, may shape individual claims-making as activist groups provide carefully crafted messages that individuals can sign and forward along to elected officials as part of larger letter-writing campaigns—campaigns that have become all the more pronounced in the digital age (Earl 2006; Earl and Kimport 2011).…”
Section: Analyzing Individual Claims-makingmentioning
confidence: 99%
See 3 more Smart Citations